Physicochemically modified high-resolution tin oxide thin film using soft imprinting. Issue 41 (20th September 2022) - Kim, Dong Hyun; Lee, Dong Wook; Oh, Jin Young; Lee, Ju Hwan; Won, Jonghoon; Jang, Jong In; Jeong, Hae-Chang; Seo, Dae-Shik
Abstract : We carried out nanoimprinting lithography on solution-processed tin oxide (SnO) film for use as a liquid crystal (LC) alignment layer, for which we used a parallel configuration. Abstract : We carried out nanoimprinting lithography on solution-processed tin oxide (SnO) film for use as a liquid crystal (LC) alignment layer, for which we used a parallel configuration. To transfer the nanostructures onto the SnO film, we conducted an experiment according to curing, from which fine nanostructures on the SnO film were obtained at a curing temperature of 200 °C. These acted as a guide for the arrangement of the LC molecules and induced geometric restriction which minimized elastic distortion energies, and so the LC molecules could be aligned in the direction of the nanostructures. The LC alignment state was investigated using polarized optical microscopy, and the pre-tilt angle was measured using a crystal rotation method. With high thermal endurance and drastically low power consumption, the nano patterned SnO was shown to be a promising candidate for LC applications. The nanopatterning process combined with nanoimprinting lithography and solution-processed inorganic materials exhibited the possibility of broadening the features of nanostructure-mounted applications, including LC devices.